An experimental study of total quality management application in learning activity: Indonesia's case study - Sabihaini; Yuli Liestyana; Widhy Tri Astuti; Muhammad Madi Bin Abdullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Babbar's study (1995) on the application of total quality management (TQM) to educational instruction in US universities has provided the idea for the current experimental study. The purpose of this study is to analyze the effectiveness of TQM implementation in Indonesian higher education educational activities. This study is a causal research that analyzes the effect of independent variable on the dependent variable. It is proposed to find the effect of TQM implementation on the effectiveness of educational activities. The data was collected with experiment methods which involved the researcher to manipulate the variables and observe for the effects. The experimental design that used in the study was a pretest and posttest experimental and control group design, therefore it utilized two group of participants (experimental and control groups). The finding of the study supports the hypothesis that TQM implementation increases the effectiveness of educational activities. TQM implementation as a treatment has a positive effect on the effectiveness of educational activities. Student's evaluation of the effectiveness of educational activities shows the higher score after the treatment.
Keywords: 330; experimental study; TQM; educational activities; Indonesia